2012
DOI: 10.1302/0301-620x.94b11.30828
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous-bilateral TKA

Abstract: In this paper, we will consider the current role of simultaneous-bilateral TKA. Based on available evidence, it is our opinion that simultaneous bilateral TKA carries a higher risk of morbidity and mortality and should be reserved for select few.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Although the authors of a recent study recommended simultaneous, rather than staged, bilateral total knee arthroplasty because of its cost effectiveness 18 , perioperative bleeding remains an important issue 19 . The effectiveness of intravenous TXA in simultaneous bilateral total knee arthroplasty was reported in previous retrospective comparative studies 20 - 22 and randomized controlled trials 15 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the authors of a recent study recommended simultaneous, rather than staged, bilateral total knee arthroplasty because of its cost effectiveness 18 , perioperative bleeding remains an important issue 19 . The effectiveness of intravenous TXA in simultaneous bilateral total knee arthroplasty was reported in previous retrospective comparative studies 20 - 22 and randomized controlled trials 15 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] The main indication for knee arthroplasty is KOA, and it has been reported that patients with bilateral knee arthritis account for more than 2/3 of patients undergoing unilateral knee arthroplasty. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“….Previous studies have shown that 1/3 of patients who underwent TKA suffered from bilateral knee joint degeneration. Twenty percent underwent contralateral TKA within 2 years following unilateral TKA [46]. Patients with bilateral arthritis requiring surgical treatment have two options: a staged procedure with a period of time between operations, and a simultaneous procedure, either sequentially by a single surgical team, or simultaneously by two surgical teams.…”
Section: Introductionmentioning
confidence: 99%